Regulation of Lipid Specific and Vitamin Specific Non-MHC Restricted T Cells by Antigen Presenting Cells and Their Therapeutic Potentials - Salio, Mariolina; Cerundolo, Vincenzo (Frontiers in Immunology, 2015)
Since initial reports, more than 25 years ago, that T cells recognise lipids in the context on non-polymorphic CD1 molecules, our understanding of antigen presentation to non-peptide specific T cell populations has deepened. It is now clear that αβ T cells bearing semi-invariant TCR, as well as subsets of γδ T cells, recognise a variety of self and non-self lipids and contribute to shaping immune responses via cross talk with Dendritic Cells and B cells. Furthermore, it has been demonstrated that small molecules derived from the microbial riboflavin biosynthetic pathway (vitamin B2) bind monomorphic MR1 molecules and activate mucosal associated invariant T cells (MAIT), another population of semi-invariant T cells. Novel insights in the biological relevance of non-peptide specific T cells have emerged with the development of tetrameric CD1 and MR1 molecules, which has allowed accurate enumeration and functional analysis of CD1- and MR1-restricted T cells in humans and discovery of novel populations of semi-invariant T cells. The phenotype and function of non-peptide specific T cells will be discussed in the context of the known distribution of CD1 and MR1 molecules by different subsets of antigen presenting cells at steady state and following infection. Concurrent modulation of CD1 transcription and lipid biosynthetic pathways upon TLR stimulation, coupled with efficient lipid antigen processing result in the increased cell surface expression of antigenic CD1-lipid complexes. Similarly, MR1 expression is almost undetectable in resting APC and it is up-regulated following bacterial infection, likely due to stabilization of MR1 molecules by microbial antigens. The tight regulation of CD1 and MR1 expression at steady state and during infection may represent an important mechanism to limit auto-reactivity, while promoting T cell responses to foreign antigens.